1977
DOI: 10.1177/004051757704700906
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Desorption of a Cationic Polymer by Human Hair: Effects of Salt Solutions

Abstract: Sorption of Polymer JR, a cationic cellulose ether, by human hair is greatly decreased in the presence of added electrolytes. This reflects the competition between cations of the added salt and the quaternary ammonium groups of the polymer for sorption sites in the substrate. In this respect the hair can be regarded as a “strong-acid” ion-exchanger, and it displays a selectivity to ions similar to that observed for conventional resin exchangers. Cations can be ranked in order according to their ability to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…With the increase in molecular weights of polymers, interactions were also increased to enhance deposition of silicone [55]. After that, Faucher, Hannah and Goddard [56][57][58] reported the application of cellulosic polymer called quaternized hydroxy ethyl cellulose (polymer-JR) and Woodard [59] employed polyethyleneimine (PEI) to improve silicone deposition on hair. The polymers with different molecular weights were studied.…”
Section: Effect Of Molecular Weightmentioning
confidence: 99%
“…With the increase in molecular weights of polymers, interactions were also increased to enhance deposition of silicone [55]. After that, Faucher, Hannah and Goddard [56][57][58] reported the application of cellulosic polymer called quaternized hydroxy ethyl cellulose (polymer-JR) and Woodard [59] employed polyethyleneimine (PEI) to improve silicone deposition on hair. The polymers with different molecular weights were studied.…”
Section: Effect Of Molecular Weightmentioning
confidence: 99%
“…The polymer JR study involved bleached hair. These data suggest that penetration is limited to about 10% of the hair after 7 days and about an order of magnitude less in unaltered hair [25]. Sorption of a higher-molecular-weight JR polymer (average molecular weight of 600,000) by bleached hair is similar to the smaller polymer by unaltered hair.…”
Section: Penetration Of Polymers Into Hairmentioning
confidence: 79%
“…Faucher et al [25] demonstrated that desorption of a polymeric cationic cellulose (polymer JR) (see Table 8.2) from hair is slower than would be expected from a simple diffusional release predicted by the square root of time law [26]. These scientists suggested that desorption of a polymer occurs only after all sites of attachment are broken.…”
Section: Desorption and Breaking Multiple Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coacervate can effectively deposit onto the hair surface, providing multiple benefits to hair [10][11][12][13][14][15]. Most conditioning shampoos depend on deposition of polymer-surfactant coacervate to confer good wet combing and manageability [16,17].…”
Section: )mentioning
confidence: 99%